Neutronics calculation of the conceptual TRISO duplex fuel rod design - Rabir M.H.; Ismail A.F.; Yahya M.S. (Elsevier Ltd, 2023)
Cylinders (shapes); High temperature reactors; Light water reactors; Oxide minerals; Thoria; Uranium dioxide; Annular fuel; Fissile materials; Fuel design; Fuel rod design; Fuel rods; Light water; Neutronics; Neutronics performance; Fuels